Fortification of pizza dough’s with whole soybean flour of new cultivar ‘UFVTN 105AP’ - Dorina Isabel Gomes Natal (Ciência Rural, 2014)
This study aimed to characterize the physicochemical properties and the correlation between the instrumental texture and the sensory acceptance of pizza dough’s fortifi ed with whole soybean fl our. Formulations were developed to contain 0%, 30%, 50% and 70% whole soybean fl our. The texture analysis indicated that the addition of 50% soybean increased (P<0.05) fi rmness, gumminess, springiness and chewiness of pizza dough. The contents of protein, dietary fi ber and and minerals calcium zinc, magnesium, potassium, copper and phosphorus were higher (P<0.05) with increasing concentration of soybean fl our. The content of lipid was higher (P<0.05) in the pizza dough with 70% whole soybean fl our. The control formulation and that containing 30% whole soybean fl our were the most accepted, being positively correlated with the instrumental texture, since it had a lower fi rmness, gumminess, springiness and chewiness. Thus, the whole soybean fl our added antioxidant minerals, protein, dietary fi ber, essential fatty acids (ω-6 and ω-3) and maintained the acceptance of the pizza dough’s, allowing to prepare food with health claim and sensory quality.